Dynamics of the Real Exchange Rate in European Emerging Economies: Evidence from Quantile Regression - Mladenović, Zorica; Bodor, Slađana (Panoeconomicus, 2018)
The sustainability of purchasing power parity (PPP) theory is examined within the quantile autoregression model for the monthly data of the euro- and the US dollar-based real exchange rate (RER) in selected European economies (the Czech Republic, Hungary, Poland, Romania, Serbia and Turkey). Period from January 2000 to December 2014 is covered. The application of quantile autoregression model is motivated by the necessity of identifying asymmetric behavior of the RER due to the shocks of different size and sign. The empirical results support to some extent the PPP theory for the euro- and US dollar-based RER in Romania, Serbia, and Turkey. The euro-based RER in Hungary and Poland is also identified to confirm the PPP theory. The dynamics of the RER in the Czech Republic cannot be associated with the PPP validity. The persistence of the euro-based RER is estimated to be more prominent after the depreciation shocks of smaller size.Key words: Purchasing power parity, Real exchange rate, Quantile regression model.JEL: C22, F31, F41.Dinamika realnog kursa u ekonomijama u nastajanju: Dokazi iz kvantitativne regresijeTeorija održivosti pariteta kupovne moći (PPP) ispituje se u okviru kvantitativnog modela autoregresije za mesečne podatke realnog kursa zasnovanog na evrima i američkom dolaru (RER) u izabranim evropskim ekonomijama (Češka, Mađarska, Poljska, Rumunija, Srbija i Turska). Pokriven je period od januara 2000. do decembra 2014. godine. Primena kvantitativnog modela autoregresije motivisana je potrebom da se identifikuju asimetrična ponašanja RER-a zbog šokova različitih veličina i znaka. Empirijski rezultati donekle podržavaju PPP teoriju za RER zasnovanom na evrima i američkim dolarima u Rumuniji, Srbiji i Turskoj. RER zasnovan na evrima takođe potvrđuje PPP teoriju u Mađarskoj i Poljskoj. Dinamika RER-a u Češkoj Republici ne može se povezati sa validnošću PPP-a. Procenjuje se da je postojanost RER-a zasnovanog na evru istaknutiji nakon šokova deprecijacije manjeg obima.Ključne reči: Paritet kupovne moći, realni kurs, kvantni regresioni model.